A randomized controlled feasibility trial exploring partnered ballroom dancing for people with Parkinson's disease. (October 2017) - Kunkel, D; Fitton, C; Roberts, L; Pickering, RM; Roberts, HC; Wiles, R; Hulbert, S; Robison, J; Ashburn, A
Objective: To determine the feasibility of a Dance Centre delivering a programme of mixed dances to people with Parkinson's and identify suitable outcomes for a future definitive trial. Design: A two-group randomized controlled feasibility trial. Methods: People with Parkinson's were randomized to a control or experimental group (ratio 15:35), alongside usual care. In addition, participants in the experimental group danced with a partner for one hour, twice-a-week for 10 weeks; professional dance teachers led the classes and field-notes were kept. Control-group participants were given dance class vouchers at the end of the study. Blinded assessments of balance, mobility and function were completed in the home. Qualitative interviews were conducted with a subsample to explore the acceptability of dance. Results: A total of 51 people with Parkinson's (25 male) with Hoehn and Yahr scores of 1–3 and mean age of 71 years (range 49–85 years), were recruited to the study. Dance partners were of similar age (mean 68, range 56–91 years). Feasibility findings focused on recruitment ( target achieved); retention (five people dropped out of dancing); outcome measures (three measures were considered feasible, changes were recommended). Proposed sample size for a Phase III trial, based on the 6-minute walk test at six months was 220. Participants described dance as extremely enjoyable and the instructors were skilled in instilling confidence and motivation. The main organizational challenges for a future trial were transport and identifying suitable dance partners. Conclusion: We have demonstrated the feasibility of conducting the study through a Dance Centre and recommend a Phase III trial.